2012
DOI: 10.5047/eps.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous observation of the electron acceleration and ion deceleration over lunar magnetic anomalies

Abstract: At ∼25 km altitude over magnetic anomalies on the Moon, the deceleration of the solar wind ions, acceleration of the solar wind electrons parallel to the magnetic field, and heating of the ions reflected by magnetic anomalies were simultaneously observed by MAP-PACE on Kaguya. Deceleration of the solar wind ions was observed for two major solar wind ion compositions: protons and alpha particles. Deceleration of the solar wind had the same E/q ( E: deceleration energy, q: charge) for both protons and alpha part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
121
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(141 citation statements)
references
References 31 publications
(28 reference statements)
19
121
1
Order By: Relevance
“…Thus, it seems plausible that if 20% reflected protons cause the formation of a new shock at an already existing shock, a similar percentage of reflected protons from the Moon could produce a new shock entirely. This does not answer the question of how the protons get reflected in the first place, but the low-altitude electric fields implied by Kaguya observations [Saito et al, 2012] and in simulations by Deca et al [2014] and others may explain the initial reflection. Eventually, a full description will have to place the very low altitude proton reflection and the generation of the shock-like structure at several tens of kilometers or higher in a self-consistent framework, but current simulations have difficulty resolving the range of scales to treat the full problem.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, it seems plausible that if 20% reflected protons cause the formation of a new shock at an already existing shock, a similar percentage of reflected protons from the Moon could produce a new shock entirely. This does not answer the question of how the protons get reflected in the first place, but the low-altitude electric fields implied by Kaguya observations [Saito et al, 2012] and in simulations by Deca et al [2014] and others may explain the initial reflection. Eventually, a full description will have to place the very low altitude proton reflection and the generation of the shock-like structure at several tens of kilometers or higher in a self-consistent framework, but current simulations have difficulty resolving the range of scales to treat the full problem.…”
Section: Discussionmentioning
confidence: 95%
“…motion of electrons and ions, help reflect solar wind protons [Saito et al, 2012]. Simulations indicate that these electric fields may form at quite low altitudes [Deca et al, 2014] and that the reflected protons can subsequently interact with the solar wind to drive a compressive interaction with similar properties to that observed by Fatemi et al [2014].…”
Section: Geophysical Research Letters Research Lettermentioning
confidence: 94%
“…The observations of the plasma particle distributions show a slowing and reversing of the flow of the protons, accompanied by a cooling upon approaching the magnetopause. Conversely, the electrons experience an acceleration toward the anomaly and heating across the transition (Saito et al 2012). The simultaneous accelerations and deaccelerations of opposite charges imply the existence of a sizeable ( -» -100 400 V m 1 ), static electric field pointing anti-Moonward above the magnetic anomaly site (Saito et al 2012).…”
Section: Lunar Swirls and Magnetic Anomaliesmentioning
confidence: 98%
“…Within the barrier, plasma is less turbulent within the diamagnetic cavity, and much of the incoming proton density has been excluded . Upstream of the narrow interface region, however, increased levels of magnetic and electrostatic turbulence, including Whistlers-modes (Halekas et al 2006;Nakagawa et al 2011), are observed, with waves occurring at or near the local lower-hybrid plasma frequency and Alfvén waves (Saito et al 2012). The source of the turbulence and waves, counter-streaming protons, is reflected back by the magnetic boundary.…”
Section: Lunar Swirls and Magnetic Anomaliesmentioning
confidence: 99%
“…We looked at possible mechanisms explaining the Aa drop around full Moon. Recent observations have established that there is an interaction on magnetically connected field lines of the solar wind and magnetospheric plasma with the Moon and its exosphere, surface, and crustal magnetic fields (e.g., Mitchell et al 2008;Poppe and Horányi 2010;Saito et al 2012; (Hapgood 2007), and the Moon enters the magnetotail typically 2-2.5 days before the full Moon. Therefore, at 3-5 days before the full Moon, when the Aa index drops are observed, the Moon is located in the magnetosheath.…”
Section: Discussionmentioning
confidence: 99%